Pengaruh Pergaulan Terhadap Pengembangan Kepedulian Sosial di Madrasah Ibtidaiyah - Meryna Putri Utami; Dyah Ayu Anggraini (STAI AL-AMIN, 2024)
This research is motivated by the phenomenon of insufficient social interaction among some students at MI Riyadlus Sholihin, where they are not fully engaged in helping others and tend to overlook their social environment. Social interaction among students is considered as one of the variables with the potential to influence the development of social concern. The aim of this study is to explore the impact of social interaction on the development of social concern among 6th-grade students at MI Riyadlus Sholihin, which is a crucial stage in adolescent development within the context of social interaction. The method employed in this research is a mixed method approach, with sample selection conducted through simple random sampling. The research instrument used is the Guttman Scale. Data analysis is carried out using simple linear regression. The results of the study indicate a significant influence of social interaction on social concern at MI. From the calculations, a significance level of 0.05 is obtained, with the calculated t-value exceeding the critical t-value (2.150 > 1.77093), and a coefficient of determination of 26.2%. Therefore, it can be concluded that there is a significant relationship between social interaction and the development of social concern at MI.